A constant area monolayer method to assess optimal lipid packing for lipolysis tested with several secreted phospholipases A2 - Yunes Quartino, Pablo Javier (2015)
We present an analysis of lipid monolayer hydrolysis at a constant area to assess the optimal lateral surface pressure value (Πopt) and thus, the surface packing density of the lipid, at which the activity of a given lipolytic enzyme is maximal. This isochoric method consists of a measurement of the decrease down to zero of the Πopt of phospholipid substrate monolayer due to continuous hydrolysis using only one reaction compartment. We performed the comparison of both approaches using several commercially available and literature-evaluated sPLA2s. Also, we characterized for the first time the profile of hydrolysis of DLPC monolayers catalyzed by a sPLA2 from Streptomyces violaceoruber and isoenzymes purified from Bothrops diporus venom. One of these viper venom enzymes is a new isoenzyme, partially sequenced by a mass spectrometry approach. We also included the basic myotoxin sPLA2-III from Bothrops asper. Results obtained with the isochoric method and the standard isobaric one produced quite similar values of Πopt, validating the proposal. In addition, we propose a new classification parameter, a lipolytic ratio of hydrolysis at two lateral pressures, 20 mN·m− 1 and 10 mN·m− 1, termed here as LR20/10 index. This index differentiates quite well “high surface pressure” from “low surface pressure” sPLA2s and, by extension; it can be used as a functional criterion for the quality of a certain enzyme. Also, this index could be added to the grouping systematic criteria for the superfamily proposed for phospholipase A2.